2005
DOI: 10.1159/000084646
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Antenatal Glucocorticoids on Circulatory Adaptation at Birth in the Ovine Fetus

Abstract: Objective: Adaptation to extra-uterine life requires dramatic increase in pulmonary blood flow. Mechanisms that induce pulmonary vasodilatation at birth are incompletely understood but include alveolar ventilation, increase in PaO2, and production of vasoactive mediators. We hypothesized that antenatal glucocorticoids (GC) increase pulmonary vasodilatation to birth-related stimuli. Study Design: To test this hypothesis, we studied the pulmonary hemodynamic response at birth to mechanical ventilation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
1
1

Year Published

2006
2006
2017
2017

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 23 publications
0
7
1
1
Order By: Relevance
“…These data contrast with our findings of a marked increase in fetal PBF in response to antenatal corticosteroids, with little or no beneficial effect on the transition of the pulmonary circulation at birth. The difference between our findings and those of previous studies (25,27) is likely because of the maturity of the fetus when exposed to corticosteroids. In previous studies, fetuses were treated at 135-138 d of gestation (25,27), whereas in our study, fetuses were treated at ϳ125 d; term is ϳ147 d.…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…These data contrast with our findings of a marked increase in fetal PBF in response to antenatal corticosteroids, with little or no beneficial effect on the transition of the pulmonary circulation at birth. The difference between our findings and those of previous studies (25,27) is likely because of the maturity of the fetus when exposed to corticosteroids. In previous studies, fetuses were treated at 135-138 d of gestation (25,27), whereas in our study, fetuses were treated at ϳ125 d; term is ϳ147 d.…”
Section: Discussioncontrasting
confidence: 99%
“…In particular, corticosteroids can increase pulmonary vascular reactivity in response to vasodilatory stimuli, including catecholamines (24,25) prostaglandins, and NO (24,26). However, previous studies found that antenatal corticosteroids have no effect on basal PBF in fetal sheep (25,27) and were considered to enhance pulmonary vasodilation induced by alveolar ventilation at birth; this effect was independent of oxygen-mediated changes. These data contrast with our findings of a marked increase in fetal PBF in response to antenatal corticosteroids, with little or no beneficial effect on the transition of the pulmonary circulation at birth.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…As catecholamines, especially norepinephrine, may play a significant role in the maintenance of the fetal pulmonary circulation and during the transitional circulation at birth, the authors speculated that corticosteroids could have a role in perinatal cardiovascular adaptation by enhancing the norepinephrine-mediated pulmonary vasodilatation. Recently, the same authors have reported that antenatal dexamethasone enhances pulmonary vasodilatation induced by alveolar ventilation at birth [9] . Similarly, it has been reported that a single dose of antenatal betamethasone enhanced relaxation of pulmonary arteries of preterm lambs induced by ␤ -adrenergic agonists and prostaglandin E 2 [10] .…”
Section: Discussionmentioning
confidence: 96%
“…Cette chute rapide des RVP est la conséquence d'une vasodilatation [7]. De multiples mécanismes contribuent à cette adaptation circulatoire à la vie extra-utérine, comme la ventilation alvéolaire, l'augmentation des pressions partielles en O 2 , les contraintes vasculaires de cisaillement (shear stress) et la libération de médiateurs vasodilatateurs [8][9][10].…”
Section: Physiopathologie De La Détresse Respiratoire Néonataleunclassified